Zeus'un Anadolu kültleri - Şahin, Nuran 1948- (Suna-İnan Kıraç Akdeniz Medeniyetleri Araştırma Enstitüsü, 2001)
Zeus (Greek deity); Anatolia; history.
Includes bibliographical references (p. [199]-218) and index
Keywords: Zeus -- Gott; Zeus (Greek deity) / Cult / Turkey; Zeus (Yunan tanrısı) - Kült - Türkiye; Zeus (Greek deity) -- Cult -- Turkey; Kult; Türkei; Anatolien